NMR characterization of the interaction of GroEL with amyloid β as a model ligand. Issue 11 (18th April 2013) - Yagi-Utsumi, Maho; Kunihara, Tomoko; Nakamura, Takashi; Uekusa, Yoshinori; Makabe, Koki; Kuwajima, Kunihiro; Kato, Koichi
Abstract : Here we report an NMR study on the substrate interaction modes of GroEL using amyloid β (Aβ) as a model ligand. We found that GroEL could suppress Aβ(1–40) amyloid formation by interacting with its two hydrophobic segments Leu17‐Ala21 and Ala30‐Val36, which involve key residues in fibril formation. The binding site of Aβ(1–40) was mapped on a pair of α‐helices located in the GroEL apical domain. These results provide insights into chaperonin recognition of amyloidogenic proteins of pathological interest. Abstract : GroEL suppresses amyloid β (Aβ) aggregation. Two hydrophobic segments of Aβ(1–40) are involved in its interaction with GroEL. Aβ(1–40) interacts with a pair of α-helices located in the GroEL apical domain.